Nucleation parameters for polymer crystallization from non-isothermal thermal analysis - Kishore, K.; Vasanthakumari, R.
Differential scanning calorimetry (DSC)has been used to obtain kinetic and nucleation parameters for polymer crystallization under a non-isothermal mode of operation. The available isothermal nucleation growth-rate equation has been modified for non-isothermal kinetic analysis. The values of the nucleation constant (Ks)and surface free energies (o, oe)have been obtained for i-polybutene-1, i-polypropylene, poly(L-lactic acid), and polyoxymethylene and are compared with those obtained from isothermal kinetic analysis; a good agreement in both is seen.
Keywords: KINETIC PARAMETERS; NUCLEATION PARAMETERS; POLYMER CRYSTALLIZATION; NON-ISOTHERMAL; THERMAL ANALYSIS; DIFFERENTIAL SCANNING CALORIMETER; HOT-STAGE MICROSCOPY